Freqüência de aglutininas anti-leptospiras em soros e pesquisa de leptospiras em rins de suínos de Minas Gerais - Fernando Antônio de Ávila (1976)
Sera obtained from 770 swine in 26 counties of the State of Minas Gerais, Brazil, were examined by the microscopic agglutination test. There were 635 (82.4%) positive reactions for one or more leptospiral serotypes at dilutions of 1:100 or higher. Based on the frequency of positives reacting será for the utilized serotypes, the serotype autumnalis (35.5%) was the most frequent, followed by wolffi (33.5%), ballum (32.9%), butembo (27.5%). bratislava (22.6%), bataviae (16.4%), javanica (13.9%), icterohaemorrhagiae (12.8%) and pomona (10.6%). Of the swine kidney samples examined by the direct imunofluorescence technique 19% were positive for inoculated with group samples from swine kidneys had agglutinating titers (1:100) in the rapid microscopic agglutination test for the serotype ballum, autumnalis and pomona. The comparative study between the rapid microscopic agglutination reactions with pathogenic leptospiras and with the L. patoc strain Patoc I in the diagnosis of swine leptospirosis revealed a statistic irregularity between the sensivity (90.6%) and specificity (26.2%) of this strain, as a screening anígen. Based on these results, L. patoc strain Patoc I would not be recommended as screening antigen for the diagnosis of swine leptospirosis.